Proteína NS4B del virus Zika : interacción con moléculas del hospedador y su rol como inmunoevasina - Sarratea, Maria Belen (2022)
Type I interferons (IFN I) are key mediators in antiviral innate immunity. During viral infections, nucleic acid sensing by intracellular receptors can trigger IFN-I production. However, many viral proteins can hinder this response. The aim of this thesis was to study the immune evasion mechanism of Zika virus NS4B protein in the IFN-I induction pathway.\nTransfections assays showed that NS4B expression inhibited IFN regulatory factors activation involved in different nucleic acid sensing cascades. NS4B correlated with lower levels of IFN-ß and IL-6 production. However, NS4B C100S mutant did not show these inhibitory effects.\nWe demonstrated that TBK1 kinase, a key component in IFN-I production pathway, is one of NS4B ligands. To further characterize this interaction, recombinant NS4B protein was expressed in bacteria and purified into micelles. TBK1-NS4B interaction was studied by surface plasmon resonance, demonstrating specific interaction.\nAltogether, these results add evidence that Zika virus NS4B would disrupt nucleic acid sensing cascade leading to an impairment of IFN-I production, highlighting the role of this viral protein in evading early immune response.